PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TEKNOLOGI INFORMASI DAN PENATAUSAHAAN KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Pemerintah Daerah Kabupaten Rejang Lebong) - Tuti Hermelinda (Universitas Prof.Hazairin,SH Bengkulu, 2018)
This study aims to find out and obtain empirical evidence regarding the influence of HRcompetencies, utilization of Information Technology and Understanding of RegionalFinancial Administration on the quality of the financial statements of the Rejang Lebongdistrict government.The research was conducted on all officials of the financial administration of the OPDof Rejang Lebong Regency using primary data obtained from questionnairesdistributed to respondents. Determination of the sample through purposive samplingand obtained a sample of 144 respondents. Data analysis using multiple regressionand hypothesis testing.The data quality test results show that all research instruments are valid and reliableand the model used is appropriate to explain the dependent variable. The resultsshowed that HR competence, utilization of Information Technology and understandingof Regional Financial Administration had a positive influence on the quality of financialstatements both partially and simultaneously